ParticipationPlus: Documenting a design process of a media architecture installation in the second digital turn era. Issue 1 (3rd April 2018) - Haeusler, M. Hank; Hespanhol, Luke; Hoggenmueller, Marius
Abstract : Purpose: The purpose of this paper is to explore through a project the feasibility of testing Carpo's preposition of the second digital turn. It further argues that if media architecture could progress into a new digital design that makes use of large amount of data, the ability of computers to filter through these data and the computers capacity to generate a physical output based on data enabled through a "digital trial and error" process and "age-old problem" in media architecture design could be addressed—in the following called Master/Slave relationship. Its breakdown is then consequently a result of applying second digital turn thinking to media architecture. Design/methodology/approach: The paper outlines two aspects to discuss the design of a media architecture installation: first, a qualitative method using the e-mail trails between the research team developing the installation to uncover trends in thought and opinion to identify if a Master/Slave outcome could have been avoided, thus it has the second digital turn thinking provided a "neutral judge". Second, a design research approach where the designed outcome of the installation is discussed and evaluated. The scope of the chapter only allows for a short overview of the design process as such. Findings: The authors could demonstrate that the design approach using second digital turn principles had overcoming the problem of a Master/Slave relationship in media architecture. Further, media architecture provides to the second digital turn, the advantage of providing input variables is of a technical nature and a clear set of objective relationships between the technical variables and constraints. Hence, it is easier to design x-number of design options. Media architecture also has advantage that the aesthetic judgement is potentially easier (which option to choose), as the primary function of most media façades lies in communicating dynamic text, graphic or images. Originality/value: The paper understands its value in opening up and contributing to the question on how to judge objectiles. When designers are now in a position to develop computer programs that can design objects how does one judge which is the best object out of all the potential options? The paper argues that if the aesthetic quality of the outcome is understood a later judgement might be easier.